Answer:
1
Step-by-step explanation:
Answer:
Step-by-step explanation:
We can use the FOIL method to simplify.
= (3x – 1)(2x + 9)
= (3x * 2x) + (3x * 9) + (-1 * 2x) + (-1 * 9)
= 6x + 27x + (-2x) + (-9)
= 33x - 11
Hope This Helped! Good Luck!
Answer:
D. 67 moons
Step-by-step explanation:
-Start with 14 moons (Neptune)
-14(moons) x 4 = 56(moons)
56(moons) + 11 more = 67 total moons for Jupiter
Answer:
Step-by-step explanation:
Give the fractions a common denominator
11/13 + 4/7 = 77/91 + 52/91
= 129/91